Problem of Small-Scale Farmers in Agricutlure Sector in Tirunelveli Taluk (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: India is an agriculture-oriented country. The country of agriculture of India towards employment is often not right recognized and well appreciated, although it provides employment to a great majority of people, that is, about 60 per cent of the country’s population. It is feeding its huge population with food grains and other food items. The food grain production is around 230 million tonnes. Agriculture is contributing to industrial development through supply of raw materials. Agriculture commodities constitute 25 per cent of India’s exports, while its share in the national income works out to be 18 per cent. The agrarian economy is the base on which the entire distorted structure of the economy and the society is constructed. Nowadays, these farming techniques are necessary as day-to-day farming lands are becoming apartments and factories. Actually, everything is happening in a contrast as for the increasing population. There should be an increase in agriculture land, but instead it is in a decreasing stage. In such a case, the awareness among the farmers is lacking. The government has to take some initiatives about such issues and appoint some persons to spread awareness about the profitable techniques of farming to uneducated farmers. Some are non-eco-friendly but we still continue the same. We must have some awareness about those things which may give profit in instant, but not an everlasting one better future.